Morphometric Analysis of Sexual Dimorphism in Penthicodes farinosus (Weber, 1801) (Hemiptera: Fulgoridae) from Sarawak: Morphometric analysis of sexual dimorphism in Penthicodes farinosus - AHMAD IRFAN ABDUL RAZAK; SITI NURLYDIA SAZALI; RATNAWATI HAZALI; FARAH NABILLAH ABU HASAN AIDIL FITRI; ISAAC STIA MARCELLINUS (Borneo Journal of Resource Science and Technology, 2023)
The Penthicodes farinosus are strikingly coloured insects and can be found in India, Myanmar, Peninsular Malaysia, Java, Sumatra, Sulawesi, the Philippines, and Borneo. Despite their wide distributional range in Asia with a common occurrence in Borneo, morphometric investigation of P. farinosus is still lacking. The study is aimed to investigate the morphological variations of this species between two different sexes in Sarawak, Malaysian Borneo. Eleven morphometric characters were measured from 183 specimens (69 males and 114 females). The data were analysed using an independent t-test, Principal Component Analysis (PCA) and Discriminant Function Analysis (DFA). Sexual dimorphism index (SDI) was found ranging from 0.044 (LV) to 0.1008 (BTg) indicating females were larger than males. In PCA, cumulative variations of 59.9% were recorded from two principal components, showing higher loadings in the length of tegmen (LTg) and total length (TL). DFA revealed a single function that explains a canonical correlation of 0.895 with 100% variation. The Wilks’ Lambda values of 0.199 were highly supported with p<0.0001. The highest loadings for the model are LTg and TL. The two variables were further tested using Leave-One-Out Cross Validation (LOOVC) method which resulted in 97.2% cases being correctly classified as male or female. This suggests LTg and TL can be useful in separating both sexes of P. farinosus.